Stabilization of ODE with hyperbolic equation actuator subject to boundary control matched disturbance - Zhou, H.C.; Guo, B.Z. (Taylor and Francis Ltd., 2019)
In this paper, we consider stabilisation for a cascade of ODE and first-order hyperbolic equation with external disturbance flowing to the control end. The active disturbance rejection control (ADRC) and sliding mode control (SMC) approaches are adopted in investigation. By ADRC approach, the disturbance is estimated through a disturbance estimator with both time-varying high gain and constant high gain, and the disturbance is canceled online in the feedback loop. It is shown that the resulting closed-loop system with time-varying high gain is asymptotically stable and is practically stable with constant high gain. By SMC approach, the existence and uniqueness of the solution for the closed loop via SMC are proved, and the monotonicity of the ‘reaching condition’ is presented. The resulting closed-loop system is shown to be exponentially stable. The numerical experiments are carried out to illustrate effectiveness of the proposed control law. © 2016, © 2016 Informa UK Limited, trading as Taylor & Francis Group.
International Journal of Control
Keywords: Active disturbance rejection control; Sliding mode control; Boundary feedback control; Stabilisation